Relation of backpack weight with Low Back Pain (LBP) Complaints in students of SMP - Aeni, Heni Fa'riatul; Herlinawati, Herlinawati; Herawati, Cucu (Riset Informasi Kesehatan; Vol 11 No 1 (2022): Riset Informasi KesehatanDO - 10.30644/rik.v11i1.491, 2022)
Abstract   Background: Using a backpack with a load that weighs â‰¥ 10% of body weight can cause Low Back Pain (LBP) complaint. This study aims to determine the relationship between backpack weight and low back pain (LBP) complaints among students of State JHS 1 Talun, Cirebon Regency. Method: This was a descriptive quantitative study with cross sectional design. The data were collected using several methods. Backpack weight was measured using a scale and low back pain (LBP) complaints were collected by means of interviews. The population of this study were all 813 students of State JHS 1 Talun Cirebon Regency in 2019, with a sample number of 89 taken using a proportional random sampling technique. Analysis of the data in this study was conducted through the Chi-Square statistical test. Results: There was a relationship between backpack weight and low back pain (LBP) complaints among students of State JHS 1 Talun, Cirebon Regency in 2019 with a P value = 0.008. Conclusion: Using a backpack with a heavy load can cause low back pain (LBP) complaints. Keywords: Backpack weight, Low back pain